Impact of noncommunicable diseases in the State of Qatar - Al-Kaabi SK; Atherton A (Dove Medical Press, 2015)
Salma Khalaf Al-Kaabi, Andrew Atherton Supreme Council of Health, Doha, Qatar Abstract: This study, commissioned by the Supreme Council of Health in the State of Qatar, focuses on the main noncommunicable diseases (NCDs) globally and regionally, in order to gauge their potential impact on Qatar. The research shows that the Gulf Cooperation Council is projected to be affected dramatically by NCDs in the coming years. The top five NCDs that will affect Qatar in terms of economic burden and disability-adjusted life years are cardiovascular diseases, mental health and behavioral disorders, cancer, respiratory diseases, and diabetes. Whilst these diseases have diverse effects on patients, their causes can be traced to “… common lifestyle-related, or behavioral, risk factors such as tobacco use, a diet heavy in fat, and physical inactivity”. The total direct and indirect costs to the Gulf Cooperation Council calculated for the above five NCDs were $36.2 billion in 2013, which equates to 150% of the officially recorded annual health care expenditure. If this trajectory is maintained, spending per head of population in Qatar will reach $2,778 by 2022. These figures demonstrate not only the potential financial impact of the main NCDs, but also give an idea of how the current health system is working to address them.Keywords: cardiovascular disease, mental health, cancer, diabetes, respiratory disease, national health strategy, State of Qatar